Physical spherical phase compensation in reflection digital holographic microscopy - Qu, Weijuan (2013)
Reflection configured digital holographic microscopy (DHM) can perform accurate optical topography measurements of reflecting objects, such as MEMs, MOEMs, and semiconductor wafer. It can provide non-destructive quantitative measurements of surface roughness and geometric pattern characterization with nanometric axial resolution in real-time. However, the measurement results may be affected by an additional phase curvature introduced by the microscope objective (MO) used in DHM. It needs to be removed either by numerical compensation or by physical compensation.